Continuous binder-free fibers of pure imogolite nanotubes - Moore,J; Paineau,E; Launois,P; Shaffer,M (ACS Applied Materials and Interfaces, 2021)
Imogolite nanotubes display a range of useful properties and provide an ideal material system to study the assembly of nanomaterials into macroscopic fibers. A method of wet spinning pure, binder-free imogolite fibers has been developed using double walled germanium imogolite nanotubes. Nanotube aspect ratio can be controlled during the initial synthesis and is critical to the spinning process. Fibers made from short nanotubes (<100 nm) have very low gel strengths, whilst dopes with longer nanotubes (500-1000 nm) are readily spinnable. The tensile behaviour of the resulting imogolite nanotube fibers is strongly influenced by relative humidity (RH), with a modulus of 30 GPa at 10% RH compared to 2.8 GPa at 85% RH, as well as a change in failure mode. This result highlights the importance of inter nanotube interactions in such assemblies and provides a useful strategy for further exploration. Interestingly, in the absence of a matrix phase, a degree of misorientation appears to improve load transfer between the individual INTs within the porous fiber, likely due to an increase of the number of inter-particle contacts. Imogolite nanotubes are an appealing analogue to other nanotube fiber systems, and it is hoped that learnings from this system can also be used to improve carbon nanotube fibers.